Analytical model of tide and river flow interaction - Somchai Rojanakamthorn; Suphat Vongvisessomjai; Wang, Tsan-Wen; Tawatchai Tingsanchali; THE STARR FOUNDATION , U. S. A. (Bangkok : Asian Institute of Technology, 1986)
The main cause of flooding in the Lower Chao Phraya River Plain which seriously damage the Bangkok city is obviously the interaction of high freshwater discharge from the north and high tides in the Gulf of Thailand. Owing to these ocean tides, the flow in the lower region of the Chao Phraya River becomes unsteady and is governed by the unsteady flow of wave hydrodynamic equations. Due to nonlinearity of the governing equations, the problems have been solved numerically only. In the present study, the governing equations are solved analytically using the approximation method of Perturbation to investigate the interaction of tide and freshwater discharge of the Chao Phraya River. The convective and nonlinear friction terms are also included in the derivations. Harmonic analysis is applied to five tidal records along the river in the years 1980 and 1983 to decompose the complicated interaction of the freshwater discharge with various constituents of tides into its individual interaction with each constituent. Four main constituents are included in this study. The relations of important dimensionless parameters of the tide, especially the dimensionless damping modulus, are then determined for each solution. The results obtained from the study show that analytical solution of dimensionless damping modulus under estimated the measured value obtained from harmonic analysis due to the weak point of mathematical approximation method of Perturbation. Therefore, modifications have been worked out to establish their correlations. Results of water level obtained by applying the analytical model to a tidal reach of the Chao Phraya River from Bangsai (km 112) to the river mouth (km O) are compared very well with those obtained from harmonic analysis.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Tides -- Mathematical models